Physiological, metabolic and ionomic responses of Solanum lycopersicum plants to Fe3O4 and FePO4 nanoparticles - Valerio Petruccelli; Emanuele Vaccarella; Emma Cocco; Francesco Mura; Domenico Rosa; Alessio Talone; Martina Iazzetta; Chiara Dal Bosco; Alessandra Gentili; Luca Di Palma; Silvia Canepari; Gabriella Pasqua; et al. (Plant Nano Biology)
Fe3O4 (NPS-M) and FePO4 (NPS-P) nanoparticles, as representative magnetic materials, have been widely used in the industrial and biomedical fields, although their use in agriculture still needs to be evaluated. The effect of NPS-M and NPS-P in tomato plants was investigated by a combination of phenotypic and metabolic approaches. Tomato plants were grown in soil treated with NPS-M and NPS-P at 0, 5, 50, 100, 500 and 1000 ppm for 8 months. Plant biomass, phenolics and carotenoids in leaves and fruits, soil pH, chlorophyll, and ionome of soil, fruits, roots and leaves, were analysed. NPS-M and NPS-P at higher concentrations increased biomass, total chlorophyll and carotenoid levels in leaves compared to controls. NPS-P caused the major soil acidification, making some nutrients more available to the roots. Although no significant differences were observed in fruit carotenoids, a significant increase in chlorogenic and luteone hexoside levels was observed after NPs treatment at low concentrations compared to controls. Inductively coupled plasma mass spectrometry (ICP-MS) revealed that both NPs compared to EDTA-based chelators resulted in differential element accumulation in roots, leaves/fruits. EDTA-based treatments increased leaf accumulation of Cr, As, K, P, while both NPs increased leaf accumulation of Ca, Co, Sr, Ti, V. Fruit accumulation of Ca, K, and Rb was higher with NPs, while Na, Mg, and P were higher with EDTA-based chelators. The obtained results offer new insights into the response of tomato plants to NPS-M and NPS-P exposure and could be useful for designing alternative strategies to the use of commercial fertilizers.